2022
DOI: 10.1002/jcsm.12954
|View full text |Cite
|
Sign up to set email alerts
|

Mapping ongoing nutrition intervention trials in muscle, sarcopenia, and cachexia: a scoping review of future research

Abstract: Muscle loss alone, or in the context of sarcopenia or cachexia, is a prevalent condition and a predictor of negative outcomes in aging and disease. As adequate nutrition is essential for muscle maintenance, a growing number of studies has been conducted to explore the role of specific nutrients on muscle mass or function. Nonetheless, more research is needed to guide evidence-based recommendations. This scoping review aimed to compile and document ongoing clinical trials investigating nutrition interventions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 101 publications
1
28
0
2
Order By: Relevance
“…Given the potential yet limited evidence on the effects of HMB supplementation in patients with cancer, future studies are needed to advance our understanding. A recent scoping review of registered clinical trials investigating nutrition interventions targeting muscle‐related outcomes revealed that 3 of 22 RCTs are evaluating the effects of HMB supplementation in this population 93 . Of these ongoing studies, dietary advice with the goal of achieving a high‐protein diet is provided in one but none are investigating the effects of HMB‐enriched ONS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential yet limited evidence on the effects of HMB supplementation in patients with cancer, future studies are needed to advance our understanding. A recent scoping review of registered clinical trials investigating nutrition interventions targeting muscle‐related outcomes revealed that 3 of 22 RCTs are evaluating the effects of HMB supplementation in this population 93 . Of these ongoing studies, dietary advice with the goal of achieving a high‐protein diet is provided in one but none are investigating the effects of HMB‐enriched ONS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review of registered clinical trials investigating nutrition interventions targeting muscle‐related outcomes revealed that 3 of 22 RCTs are evaluating the effects of HMB supplementation in this population. 93 Of these ongoing studies, dietary advice with the goal of achieving a high‐protein diet is provided in one but none are investigating the effects of HMB‐enriched ONS. Notably, it is also unclear if other strategies are being used to optimize nutritional status in these studies, which may make it difficult to fully evaluate the effect of HMB in mitigating muscle and function loss, especially in patients with cancer who develop malnutrition along the course of the study.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines and expert consensus recommend appropriate and timely nutritional evaluation and specific approaches to improve clinical outcomes in subjects at higher risk of developing nutritional problems, including subjects with chronic and/or severe diseases in different healthcare settings [ 6 , 15 , 16 ]. The present study suggests and confirms the importance of nutritional supplementation in subjects suffering from an infection and catabolic disease, such as COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, nutrients such as protein/amino acids, vitamin D, n-3 polyunsaturated fatty acids (n-3 PUFA), b-hydroxy-b-methylbutyrate (HMB), and polyphenols can support muscle health and recovery by affecting both muscle and immune function, demonstrating the interaction between muscle and immune systems. These are and other nutritional strategies are actively being explored in nutrition intervention trials focusing on muscle mass, sarcopenia and cachexia [160]. Because achieving nutritional intake goals in older adults and clinical populations may be challenging, individualized nutritional counseling should be offered concurrent to nutrition therapy, as endorsed by nutrition care guidelines [161,162].…”
Section: Can We Prevent or Revert Muscle Loss And Malnutrition With N...mentioning
confidence: 99%
“…Furthermore, more research is required to explore the impact of nutrition and exercise interventions to maximize anabolic potential, physical performance, and outcomes in healthy aging, and acute and chronic disease, including acute conditions like COVID-19. Recommendations for future nutrition trials have been provided in order to rapidly advance knowledge translation of interventions addressing muscle, sarcopenia and cachexia to clinical practice [160].…”
Section: Outlook On Future Researchmentioning
confidence: 99%